2014
DOI: 10.1016/j.neulet.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin release by the lateral olivocochlear efferents may inhibit auditory nerve activity: A cochlear drug delivery study

Abstract: Dynorphin (dyn) is suggested to excite the auditory nerve (AN) when released by the lateral olivocochlear (LOC) efferents. However, previous studies evaluated either intravenously delivered dyn-like agents, raising the potential for systemic (central) effects, or agent concentrations unlikely to be achieved via endogenous cochlear release. This study tested the hypothesis that biologically relevant increases in dyn levels in the cochlea achieved via diffusion of the drug of (−)pentazocine across the round wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…below). Furthermore, and in support of our hypothesis it has been shown that the lateral olivocochlear bundle could provide the required noise input to the AN, as disruption of lateral olivocochlear neurons with a dopaminergic neurotoxin depressed spontaneous auditory nerve activity (Le Prell et al, 2014) and efferent synapses of the lateral olivocochlear bundle re-innervate IHCs of the aged cochlea (Lauer et al, 2012). …”
Section: Discussionsupporting
confidence: 80%
“…below). Furthermore, and in support of our hypothesis it has been shown that the lateral olivocochlear bundle could provide the required noise input to the AN, as disruption of lateral olivocochlear neurons with a dopaminergic neurotoxin depressed spontaneous auditory nerve activity (Le Prell et al, 2014) and efferent synapses of the lateral olivocochlear bundle re-innervate IHCs of the aged cochlea (Lauer et al, 2012). …”
Section: Discussionsupporting
confidence: 80%
“…As the stimulus level decreased, the derived estimates of f Tr linearized and the slope steeped at 0 Pa (or the operating point). Ouabain applied to the round window markedly reduced neural excitation in the basal half of the cochlear spiral, consistent with the idea that solutions applied to the cochlear base are limited to treating only the basal half of the cochlear spiral (Salt and Ma, 2001;Chen et al, 2005;Le Prell et al, 2014), increasing the magnitude but not the general sigmoidal saturating morphology of derived f Tr estimates.…”
Section: A Harmonic Analysis Applied To Cochlear Responsessupporting
confidence: 77%
“…In addition to classical neurotransmitters, dynorphin may modulate the neural output of the cochlea as the CAP amplitude is depressed following diffusion of the kappa-opioid receptor agonist (−) pentazocine across the round window membrane (Le Prell et al 2014). Finally, CGRP application increases the spike rate and decreases the mechanically driven response of primary afferents in the lateral line (Bailey and Fig.…”
Section: Control Of Auditory Nerve Fiber Excitability In the Adult Comentioning
confidence: 99%